Contribution of NRG1 Gene Polymorphisms in Temporal Lobe Epilepsy. (March 2016) - Zhu, Wen-Ye; Jiang, Pei; He, Xin; Cao, Ling-Juan; Zhang, Li-Hong; Dang, Rui-Li; Tang, Mi-Mi; Xue, Ying; Li, Huan-De
The purpose of the present study was to investigate the possible association between temporal lobe epilepsy and NRG1 gene polymorphisms. A total of 73 patients and 69 controls were involved in this study. Genomic DNAs from the patients and controls were genotyped by polymerase chain reaction-ligase detection reaction method. There was an association of rs35753505 (T>C) with temporal lobe epilepsy (χ 2 = 6.730, P = .035). The frequency of risk allele C of rs35753505 was significantly higher (69.9%) in patients compared to controls (55.8%) (χ 2 = 6.023, P = .014). Interestingly, the significant difference of NRG1 genotype and allele frequency only existed among males, but not females. In addition, no statistically significant association was found between rs6994992, rs62510682 polymorphisms, and temporal lobe epilepsy. These data indicate that rs35753505 of NRG1 plays an important role in conferring susceptibility to the temporal lobe epilepsy in a Chinese Han population.